Understanding telehealth adoption among healthcare professionals in Saudi Arabia through an extended technology acceptance model - Al-jasim, Batool; Baklouti, Emna; Elsayed, Ebtesam; Ouanes, Khaled (Privietlab, 2025)
The COVID-19 pandemic has accelerated the global shift toward telehealth services, compelling healthcare systems to integrate digital platforms for continued patient care. This study investigates the factors influencing the adoption of telehealth applications among healthcare professionals (HCPs) in Saudi Arabia, using an extended Technology Acceptance Model (TAM). The model incorporates classical TAM variables, such as perceived usefulness and ease of use, alongside additional quality dimensions, such as learnability, interface quality, interaction quality, and reliability. Data were collected from 102 HCPs across public and private hospitals and analyzed using Structural Equation Modeling with SmartPLS. The results revealed that perceived usefulness, learnability, interaction quality, and reliability significantly influence satisfaction, which in turn strongly predicts future usage intention. However, ease of use and interface quality were found to be non-significant, suggesting that, under pandemic conditions, functional reliability and clinical value outweigh usability aesthetics. The model demonstrated substantial explanatory power (R² = 0.691 for satisfaction; R² = 0.623 for intention) and predictive relevance through PLSpredict. This research extends the TAM by integrating system quality factors relevant to healthcare contexts and offers practical insights for policymakers and system developers aiming to enhance the long-term adoption of telehealth technologies.